2022
DOI: 10.1186/s42269-022-00857-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of iro B, stn and hil A virulence genes in Salmonella enterica serovar typhimurium from non-ripened cheese

Abstract: Background Microorganisms' survival is based on the importance of growth factors found in the microbial environment, as well as their overwhelming appetite for survival which is controlled by their genetic material. This study was designed to investigate the virulence patterns of Salmonella enterica serovar typhimurium associated with soft cheese. Two hundred and sixty (260) soft cheese samples were collected from vendors at Akure, Ikare and Owo in Ondo State, Nigeria. Molecular characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In the current study, the spvC gene was found to be restricted to all S. Typhimurium serotypes, and it is consistent with the findings of Zou et al [28] and Elzhraa et al [23]. However, a prior study on non-ripened cheese by Oladapo et al [20] from Nigeria identified S. Typhimurium isolates as stn and hilA positive, but spvC-negative, which is in contrast with our current research. The limited incidence of spvC-positive strains in our study may be attributed to the unstable plasmid-located genes, which are lost through repeated sub-culturing steps [29,30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the spvC gene was found to be restricted to all S. Typhimurium serotypes, and it is consistent with the findings of Zou et al [28] and Elzhraa et al [23]. However, a prior study on non-ripened cheese by Oladapo et al [20] from Nigeria identified S. Typhimurium isolates as stn and hilA positive, but spvC-negative, which is in contrast with our current research. The limited incidence of spvC-positive strains in our study may be attributed to the unstable plasmid-located genes, which are lost through repeated sub-culturing steps [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Unsafe water sources in the Nile Delta regions, unsanitary conditions in food production environments, poor personal hygiene, and the health status of food handlers increase the risk of cross-contamination of retail food with virulent and AMR enteropathogenic bacteria, which could be a potential vehicle for foodborne diarrheal illnesses [12,19,20]. To date, limited studies have addressed the occurrence of virulence and β-lactams resistance genes in Salmonella strains isolated from Rumi and pasteurized Kariesh cheeses across rural areas in Lower Egypt, particularly in the Nile Delta region.…”
Section: Discussionmentioning
confidence: 99%